2016
DOI: 10.1002/cphc.201600149
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Scattering of Aromatic and Aliphatic Liquids

Abstract: Organic solvents, such as cyclohexane, cyclohexene, methylcyclohexane, benzene and toluene, are widely used as both reagents and solvents in industrial processes. Despite the ubiquity of these liquids, the local structures that govern the chemical properties have not been studied extensively. Herein, we report neutron diffraction measurements on liquid cyclohexane, cyclohexene, methylcyclohexane, benzene and toluene at 298 K to obtain a detailed description of the local structure in these compounds. The radial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
88
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(100 citation statements)
references
References 41 publications
(100 reference statements)
11
88
1
Order By: Relevance
“…This, together with simulation based structure refinement, for example Empirical Potential Structure Refinement (EPSR), 52 allows spatial and orientational correlations in liquids to be studied in unprecedented detail. Our previous neutron scattering study of liquid benzene, 42 later confirmed by Falkowska et al, 50 shows that benzene prefers perpendicular nearest neighbours in a Y-shaped geometry. Parallel displaced geometries are present as a shoulder in the correlation surface, but are not the dominant interaction.…”
Section: 17mentioning
confidence: 51%
See 2 more Smart Citations
“…This, together with simulation based structure refinement, for example Empirical Potential Structure Refinement (EPSR), 52 allows spatial and orientational correlations in liquids to be studied in unprecedented detail. Our previous neutron scattering study of liquid benzene, 42 later confirmed by Falkowska et al, 50 shows that benzene prefers perpendicular nearest neighbours in a Y-shaped geometry. Parallel displaced geometries are present as a shoulder in the correlation surface, but are not the dominant interaction.…”
Section: 17mentioning
confidence: 51%
“…This should be shown in contrast to benzene, 42,50 where although a parallel arrangement of the molecules is seen as a shoulder in the angular radial distribution function, it is not a local maximum. It also should be noted that perpendicular nearest neighbours are a local maximum in the data, and of a similar height as seen in liquid benzene.…”
Section: Liquid Naphthalene At 85 8cmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Solvation as studied through neutron diffraction is a wide-ranging and active subject with applications in many fields ranging from physical chemistry to biochemistry. [21][22][23][24][25][26][27] In addition to the AB-ammonia interactions, a more fundamental interest in the nature of solvation in such a (di)hydrogen bondrich environment sparks our study of these systems. Insight into the AB-AB intermolecular interactions is a further goal for this work.…”
mentioning
confidence: 99%
“…[7,8] MCM-41 is an idealized model catalyst support formed from aporous silica glass,comprising ahexagonally organized lattice of cylindrical pores.F or the system under investigation, features corresponding to the regular ordering of the pore network can be observed via Bragg scattering peaks in the low-Q range (corresponding to correlations at longer real-space distances) of the total structure factor (Figure 1), whilst the diffuse scattering arising from the liquid present in the pores,f rom Figure 1. [17] Figure 1s hows the total structure factor obtained from the EPSR simulation filled with benzene-d 6 compared with experimental data. Dotted line expresses the experimental data while the solid line shows that generated by Empirical Potential Structure Refinement (EPSR) followingconstraint by the experimental data.…”
mentioning
confidence: 99%